Implementasi Kebijakan Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan Di Kabupaten Sinjai - Bakhri, Syamsul; Nurdin, Mochamat; Fitrawati AB (Program Studi Administrasi Publik, 2025)
This research aims to analyze the implementation of the policy of Law No.16 of 2019 concerning Marriage in Sinjai Regency. This law regulates changes to the minimum age limit for marriage from 16 years for women to 19 years for both women and men. This research uses a qualitative approach with descriptive methods, which aims to describe in depth the implementation of this policy at the district level, as well as the factors that influence it. Data was collected through interviews with related parties such as the Head of the District Ministry of Religion Office. Sinjai, officials at the KUA (KUA North Sinjai, South Sinjai and TellulimpoE), the Religious Courts, and the community. The research results show that the implementation of this policy in Sinjai Regency still faces various challenges, including a lack of public understanding of changes to the law, limited resources in socialization, and a culture that still prioritizes traditional norms regarding marriage age. However, this policy has started to have a positive impact in reducing the rate of early marriage, although it is not yet completely effective. This research suggests the need for increased outreach and support from various parties to realize the objectives of the law.